JURIDICAL ANALYSIS OF THE EMPLOYMENT RELATIONSHIP REGULATION CONCERNING PARENTING BY BABYSITTER - Utama, Gwendolyn Ingrid; Marpaung, Satrya Pangadaran (Faculty of Law, Universitas Sebelas Maret, 2018)
The need for childcare service is a phenomenon in households where parents can not function to nurture children on a full-time basis. Children, especially at the age of golden age, is an